Preparation method of nanometer immobilized layer-by-layer self-assembled DAC CO2 capturing photosynthetic agent

The nano-solid-load layer-based self-assembly technology covers 5-ALA, which solves its stability and dose sensitivity in the environment, significantly improves the efficiency and stress resistance of plants, and achieves a more efficient plant growth promotion effect .

CN119111531APending Publication Date: 2024-12-13BEIJING FAIRVIEW NEW TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411260053.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

5-ALA has poor stability in the environment and is susceptible to factors such as light, temperature and pH, which leads to degradation or loss of activity. The conditions for use are harsh and the dose is sensitive, which affects its effectiveness in field applications.

Method used

Using nano-solid-carrying layer-based self-assembly method, 5-ALA or its derivatives are coated in a multi-layer polymer material, and it is firmly connected to the support surface through electrostatic interactions and chemical reactions to form a stable multi-layer structure, improve its stability and bioavailability in the external environment.

Benefits of technology

It significantly improves the stability and bioavailability of 5-ALA, extends its validity period, achieves a more efficient and controllable plant growth promotion effect, and enhances photosynthesis efficiency and stress resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005035280150000151
    Figure BDA0005035280150000151
  • Figure BDA0005035280150000152
    Figure BDA0005035280150000152
  • Figure BDA0005035280150000161
    Figure BDA0005035280150000161
Patent Text Reader

Abstract

The invention relates to a preparation method of a nano immobilized layer-by-layer self-assembled DAC CO2 capturing photosynthetic agent. The preparation method comprises the following steps: adsorbing a nano particle carrier to form a 5-ALA initial layer; sequentially and alternately depositing high polymer materials with opposite charges according to positive and negative charges on the surface of the 5-ALA initial layer, and stirring and self-assembling to form coated 5-ALA coated with multiple layers of high polymer materials; and adding the coated 5-ALA into a cross-linking agent solution, carrying out a cross-linking reaction on the cross-linking agent and a film layer polymer group to form a cross-linked structure, and drying to obtain the nano immobilized layer-by-layer self-assembled DAC CO2 capturing photosynthetic agent. According to the invention, layer-by-layer self-assembly is carried out, 5-ALA or a derivative thereof is firmly connected to the surface of the carrier and multi-layer coating is carried out, so that the loading capacity of the enhancer is increased, the 5-ALA is effectively protected from being influenced by external environment, such as photolysis or degradation, the validity period of the enhancer in application is prolonged, the performance of aminolevulinic acid (5-ALA) as a photosynthetic enhancer can be remarkably improved, and the application prospect is wide. And a more efficient and controllable plant growth promoting effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a photosynthesis agent, and in particular to a nano-solid-supported layer-by-layer self-assembled DAC CO capture agent. 2 The invention discloses a method for preparing a photosynthesis agent, belonging to the technical field of plant photosynthesis agents. Background Art

[0002] Photosynthesis is an extremely critical physiological process in the growth process of plants. It is not only the main way for plants to obtain energy, but also directly affects the yield and quality of plants. The efficiency of photosynthesis directly determines the biomass accumulation of plants. Organic matter such as sugar produced by photosynthesis is the main raw material for the development of fruits and seeds. Adequate photosynthesis can promote fruit expansion and increase sugar accumulation, thereby improving the quality and taste of fruits. In addition, it can also increase the plumpness and germination rate of seeds, directly affecting the quality and yield of crops. Photosynthesis has an important influence on the synthesis of secondary metabolites in plants. These secondary metabolites, such as vitamins, aromatic substances and antioxidants, are directly related to the nutritional value and flavor of plant products. For example, under conditions of high photosynthesis intensity, the vitamin C content in plants is usually higher, thereby improving the quality of agricultural products. Plants with sufficient photosynthesis usually have stronger stress resistance. Photosynthetic products provide plants with sufficient energy and material basis, enabling them to better cope with environmental stresses such as drought, salinity and pests and diseases. Plants with strong stress resistance can not only increase yields, but also ensure the stability of quality.

[0003] 5-ALA (5-aminolevulinic acid) is an essential substance for organisms to synthesize chlorophyll, heme, vitamin B12, etc. It is also an important intermediate in organic synthesis. By promoting chlorophyll synthesis and optimizing the activity of photosynthesis-related enzymes, 5-ALA can enhance the photosynthetic capacity of plants, thereby increasing the efficiency of carbon dioxide fixation. 5-ALA is a compound that exists naturally in plants, animals and microorganisms. Its application will not have a negative impact on the environment and meets the needs of sustainable agriculture.

[0004] 5-ALA can directly participate in the synthesis of plant chlorophyll and increase the chlorophyll content, thereby enhancing the photosynthesis efficiency and improving the utilization rate of light energy in plants. As a photosynthesis promoter, aminolevulinic acid (ALA) can significantly improve the photosynthesis efficiency of plants, thereby enhancing the ability of plants to assimilate carbon dioxide. 5-ALA can enhance the resistance of plants to adversities (such as drought, salt damage, low temperature, high temperature, etc.). This is mainly because 5-ALA can regulate the antioxidant system in plants and improve the antioxidant capacity of plants; the use of low concentrations can generally produce significant results, reducing agricultural production costs and avoiding the risk of toxicity that may be caused by high concentrations of chemicals.

[0005] However, there are some defects and deficiencies in its preparation and application, mainly manifested in 1) stability issues. 5-ALA has poor stability in the environment and is easily affected by environmental factors such as light, temperature and pH value, resulting in degradation or loss of activity. 5-ALA is easily degraded under light, which limits its effect stability when applied in the field. Under strong light conditions, the active ingredients of 5-ALA will degrade rapidly, thus affecting its effect of promoting photosynthesis. 2) Limitation of application methods. The application method of 5-ALA needs to be carefully considered. Its absorption and utilization efficiency in plants is affected by many factors, such as the dosage, time and environmental conditions of application. If it is not applied properly, it may lead to poor effects and may even have a negative impact on plants. 3) Dose sensitivity. The effect of 5-ALA is closely related to the dosage used. Too high or too low a dose will affect its effect. Too high a dose may cause photooxidative damage to plants and lead to growth inhibition; too low a dose may not have the expected enhancement effect. Therefore, how to accurately control the dosage used is a major challenge in application. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a nano-solid layer-by-layer self-assembled DAC CO capture 2 The preparation method of the photosynthesis agent solves the problems in the prior art that 5-ALA has poor stability in the environment and is easily affected by environmental factors such as light, temperature and pH value, resulting in its degradation or loss of activity, harsh use conditions and dose sensitivity.

[0007] The technical solution of the present invention to solve the above technical problems is as follows: a nano-solid layer-by-layer self-assembled DAC CO capture 2 The preparation method of the photosynthesis agent comprises the following steps: step (1), dispersing a nanoparticle carrier in a buffer solution, adding a positively charged polymer solution or a negatively charged polymer solution to obtain a nanomaterial with a polymer adsorbed on the surface, and adding 5-ALA or its derivatives under stirring to form an initial layer of 5-ALA;

[0008] Step (2), according to the positive and negative surface charges of the 5-ALA initial layer in step (1), polymer materials with opposite charges are deposited alternately in sequence, and stirred for self-assembly to form coated 5-ALA coated with multiple layers of polymer materials;

[0009] Step (3), adding the coated 5-ALA in step (2) to a crosslinking agent solution, the crosslinking agent reacts with the polymer groups of the membrane layer to form a crosslinked structure, and drying to obtain a nano-solidified layer-by-layer self-assembled DAC CO capture 2 Photosynthetic agent.

[0010] The beneficial effects of the present invention are as follows: through the layer-by-layer self-assembly of the present invention, an initial layer is set, and the electrostatic interaction between the nanomaterial and the carrier or template is utilized to uniformly deposit the nanoparticles on the template surface. Then, through multi-layer covalent bonding or chemical reaction, such as the reaction of hydroxyl groups and amino groups with functional groups on the nanoparticles, 5-ALA or its derivatives are firmly connected to the carrier surface and multi-layer coating is performed, thereby increasing the load of the enhancer, effectively protecting 5-ALA from external environmental influences, such as photolysis or degradation, thereby extending its effective period in application, and significantly improving the performance of aminolevulinic acid (5-ALA) as a photosynthetic enhancer, achieving a more efficient and controllable plant growth promotion effect.

[0011] Specifically, step (1) disperses the nanoparticles in a buffer solution with a pH value of 5.0-7.5 at a concentration of 5 mg / mL-10 mg / mL, adds 1 mg / mL of a charged polymer solution, and stirs for 12 hours to allow the charged polymer to adsorb on the surface of the nanomaterial, and then adds 1 mg / mL of 5-ALA with stirring, reacts for 6 hours, and forms an initial 5-ALA layer.

[0012] Step (2), alternately depositing polymer materials with opposite charges; specifically, depositing polymer materials with (negative and positive) charges in sequence according to the surface (positive and negative) charges of the initial layer of 5-ALA, the charged polymer material aqueous solution is 1 mg / mL, pH 7.0, and is fully mixed using a magnetic stirrer to form a first layer of coating; after each deposition, the unadsorbed polymer material is washed with deionized water to ensure the integrity of each layer; then the mixture is added to the first layer of polymer material aqueous solution with opposite charges of 1 mg / mL, pH 7.0, and stirred and allowed to stand to form a second layer of polymer material coating. Alternate deposition, each layer reacts for 30 minutes, can be repeated 4-10 times, and finally a multilayer structure is formed, and the supernatant is discarded using a centrifuge (8000 rpm, 10 minutes) to separate the 5-ALA coated with the multilayer structure.

[0013] The present invention uses the initial layer of nanocarrier 5-ALA as the base layer for layer-by-layer self-assembly (LbL). The initial layer provides a stable and reactive surface for subsequent self-assembly, so that a multilayer structure can be constructed by alternately adsorbing polyelectrolytes or other molecules with opposite charges.

[0014] The present invention selects molecules or polymers with specific functional groups as the initial layer, and these functional groups can chemically or physically adsorb with the subsequent interlayer materials. For example, if the initial layer has positively charged amino functional groups, negatively charged polyelectrolytes can be adsorbed by electrostatic action to form a new layer of material. Next, another positively charged polyelectrolyte can be adsorbed to form a second layer, and this process can be repeated to build a multilayer structure; that is, by alternately depositing 5-ALA and functional molecules with opposite charges, a stable multilayer structure can be formed. This process increases the local concentration of 5-ALA, allowing it to play a more efficient role in photosynthesis.

[0015] The present invention improves the stability of 5-ALA in external environments such as light and heat by coating it in a multilayer structure, and reduces its degradation during storage and use. At the same time, by controlling the interaction between the layers, the release rate of 5-ALA can be adjusted, further improving its bioavailability in plants. By co-assembling other functional molecules, synergistic effects of different functions can be achieved.

[0016] Based on the above technical solution, the present invention can also be improved as follows.

[0017] Furthermore, the nanoparticle carrier in step (1) is gold nanoparticles (AuNPs), iron oxide nanoparticles (Fe 3 O 4 NPs)Silica nanoparticles (SiO 2 NPs), polylactic acid-co-glycolic acid nanoparticles (PLGANPs), silver nanoparticles (AgNPs), carbon nanotubes (CNTs), zinc oxide nanoparticles (ZnONPs).

[0018] Furthermore, the buffer in step (1) is any one of phosphate buffer (PBS, pH 7.4), acetate buffer (AcB, pH 5.0), HEPES buffer (pH 7.2), Tris-HCl buffer (pH 7.4), sodium citrate buffer (SCB, pH = 5.0), Triton X-100 (pH 7.0), and sodium acetate-acetic acid buffer (NaAc / HAc, pH 4.79).

[0019] Furthermore, the nanoparticle carrier is dispersed in the buffer solution at a mass volume concentration of 5 mg / mL-10 mg / mL.

[0020] Furthermore, the polymer material in the positively charged polymer solution in step (1) or step (2) is any one of chitosan, polyethyleneimine (PEI), polydimethyldiallyl ammonium chloride (PDDA), poly-L-lysine (PLL), polyvinyl alcoholamine (PVAm), poly(4-vinylpyridine) (P4VP), and poly(2-acrylamidoethylamine) (PAEE); the polymer material in the negatively charged polymer solution is any one of sodium alginate (SA), sodium hyaluronate (SH), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC), sodium polystyrene sulfonate (PSS), sodium polyacrylamide sulfonate (PAMPS), and sodium polyglutamate (γ-PGA).

[0021] Furthermore, the positively charged polymer solution is an ethanol solution of a polymer material, and the ethanol solution may be a deionized water solution of 10% ethanol; and the negatively charged polymer solution is a deionized water solution of a polymer material.

[0022] Furthermore, the mass volume concentration of the positively charged polymer solution or the negatively charged polymer solution is 1 mg / mL, and both are adjusted to a pH value of 6.5-7.5, preferably 7, using a NaOH solution or a HCl solution.

[0023] Furthermore, the cross-linking agent in step (3) is any one of glutaraldehyde (GA), formaldehyde (HCHO), ethylenediamine (EDA), dithiodibenzoic acid (DSS), N-ethyl-N'-(3-dimethylaminopropyl)carbodiimide (EDC), ethylene glycol dimethacrylate (EGDMA), and 4-nitroanisole (PNB).

[0024] Furthermore, the mass percentage concentration of the cross-linking agent is 5.0%.

[0025] Furthermore, the cross-linking reaction in step (3) is carried out at room temperature for 1-2 hours. After the reaction is completed, the multilayer film with a cross-linked structure is taken out from the cross-linking agent solution, thoroughly washed with deionized water, and dried naturally, ventilated or at a low temperature below 50°C. Specifically, 100 mL of deionized water can be taken, 5.0 grams of cross-linking agent can be added, and stirred evenly. A 5.0% cross-linking agent aqueous solution is prepared, and the 5-ALA coated with the multilayer structure constructed in step (2) is completely immersed in the cross-linking agent solution to ensure that the film layer is in full contact with the cross-linking agent; the reaction time is 1 hour at room temperature. During this period, the cross-linking agent reacts chemically with the reactive groups in the film layer to form a cross-linked structure. After the reaction is completed, the multilayer film is taken out from the cross-linking agent solution, and thoroughly washed with a large amount of deionized water to remove the unreacted cross-linking agent; after washing, it is placed in a ventilated and dry environment to dry naturally or dried at a low temperature below 50°C until completely dry to obtain a nano-solidified layer-by-layer self-assembled DAC CO capture 2 Photosynthetic agent.

[0026] The present invention can (1) encapsulate 5-ALA in nanoparticles or other carriers through layer-by-layer self-assembly to reduce its degradation under light, temperature or enzymatic hydrolysis. This encapsulation form helps to control the release rate of 5-ALA in plants, so that it can continue to play a role in the key stage of photosynthesis.

[0027] (2) Increase chlorophyll content. 5-ALA is a precursor for chlorophyll synthesis. Enhancing its utilization in plants can directly promote chlorophyll synthesis. By precisely controlling the release of 5-ALA, layer-by-layer self-assembly technology can maximize the chlorophyll content of plants, thereby enhancing photosynthesis efficiency.

[0028] (3) Improve photosynthetic rate. The increase in chlorophyll content directly promotes the light capture efficiency in photosynthesis, which significantly improves the photosynthetic rate. In addition, 5-ALA participates in various physiological processes, such as cellular respiration and antioxidant defense, which can also indirectly support the improvement of photosynthetic rate.

[0029] (4) Improve stomatal conductance, which is an important indicator for plants to regulate gas exchange and is closely related to photosynthesis. The layer-by-layer self-assembly technology helps 5-ALA act on plants in a slow-release manner, can precisely control the distribution of 5-ALA at the nanoscale, and can directly guide it to the photosynthetic reaction center in the plant chloroplasts, thereby improving its utilization rate and significantly enhancing the photosynthetic efficiency of plants; it can improve the regulation of stomatal opening and closing, optimize gas exchange efficiency, and thus enhance the overall photosynthetic capacity.

[0030] The cross-linking treatment of the present invention is a process of forming covalent bonds between polymer chains through chemical reactions, thereby constructing a three-dimensional network structure. This method is commonly used to improve the mechanical strength, chemical stability and thermal stability of materials. Cross-linking agents play a key role in this process. They connect different polymer chains together through reactive functional groups to form a stable network structure. After cross-linking treatment, the overall stability and mechanical strength of the membrane are greatly improved. Although the water permeability and 5-ALA loading may decrease slightly, it can still maintain relatively good performance and is suitable for long-term stable release of 5-ALA photosynthesis agent.

[0031] The core function of the cross-linking treatment is to enhance the physical and chemical properties of the multilayer film through chemical cross-linking reactions, thereby improving the stability and bioavailability of the 5-ALA photosynthetic agent. This treatment step is of great significance for improving the release control of the photosynthetic agent, extending the action time, and improving safety and economic benefits.

[0032] (1) Enhance the stability of the multilayer film. The crosslinker chemically reacts with the functional groups in the multilayer film to form covalent bonds, thereby connecting the different layers of film materials together. This crosslinking effect significantly improves the mechanical strength, chemical stability and hydrolysis resistance of the film. Improving the stability of the multilayer film can prevent the degradation or rupture of the film due to environmental factors (such as water, heat, acidic and alkaline conditions, etc.) during storage or application. This is crucial to improving the durability and stability of the 5-ALA photosynthetic agent.

[0033] (2) Improve the release control of photosynthetic agents. Cross-linking treatment can adjust the pore size and density of the multilayer membrane, thereby affecting the release rate of 5-ALA photosynthetic agent. Membranes with a higher degree of cross-linking will be denser, which helps to delay the release of the drug; while membranes with a lower degree of cross-linking may promote faster release. By controlling the release rate of 5-ALA, the photosynthetic agent can be continuously released in the target tissue, prolonging its effective action time and improving the photosynthetic therapeutic effect. At the same time, it can also reduce the occurrence of side effects. (3) Improve the biocompatibility of the membrane. The cross-linking agent can not only enhance the physical and chemical properties of the multilayer membrane, but also improve the biocompatibility of the membrane and reduce the immune rejection or toxicity of the membrane material to the organism. Good biocompatibility is crucial for the effective application of photosynthetic agents. Cross-linking treatment can reduce the mutual rejection between the membrane material and the tissue, and increase its stability and safety in the body. (4) Extend the storage period. The multilayer membrane after cross-linking treatment has higher mechanical strength and chemical stability, and can maintain its structure and function under storage conditions, and is not prone to denaturation or degradation. This has important economic significance for the large-scale production and application of 5-ALA photosynthetic agent. Through cross-linking treatment, the shelf life of the product can be extended and loss and waste can be reduced. DETAILED DESCRIPTION

[0034] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0035] Example 1

[0036] Nano-supported layer-by-layer self-assembled DAC for CO capture 2 The preparation method of the photosynthesis agent comprises the following steps:

[0037] Preparation of the initial layer 5-ALA: Fe 3 O 4 NPs were dispersed in PBS buffer with a pH value of 7.4 at a concentration of 10 mg / mL, and PEI solution of 1 mg / mL was added and stirred for 12 hours. 5-ALA was added to the dispersion at a concentration of 1 mg / mL and stirred for 12 hours to adsorb 5-ALA on the nanoparticles Fe 3O 4 NPs surface, forming a 5-ALA initial layer; adjusting the pH of the 5-ALA initial layer solution to 7.0 to ensure its stability;

[0038] Layer-by-layer self-assembly of 5-ALA initial layer: Dissolve PEI in a 10% ethanol deionized water solution to obtain a PEI polymer solution with a concentration of 1 mg / mL; use 1M NaOH solution to adjust the pH value to 7.0. Dissolve PAA in ethanol deionized water to obtain a PAA polymer solution with a concentration of 1 mg / mL. Use 1M HCl solution to adjust the pH value to 6.5;

[0039] Add PAA (1 mg / mL, pH 6.5) solution to the surface of the initial layer of 5-ALA, mix thoroughly with a magnetic stirrer, and let it stand to form the first layer of PAA coating. Use deionized water to wash the unadsorbed PAA to ensure the integrity of each layer. Then add the mixture to the PEI (1 mg / mL, pH 7.0) polymer material aqueous solution, stir and stand in the same way to form the second layer of PEI coating. Alternate deposition, each layer reacts for 30 minutes, repeat 6 times, and finally form a multilayer structure. Use a centrifuge (8000 rpm, 10 minutes) to discard the supernatant and separate the 5-ALA coated with the multilayer structure.

[0040] GA treatment to obtain layer-by-layer assembled 5-ALA photosynthesis enhancer: Take 100 mL of deionized water, add 5.0 grams of GA, and stir evenly. Prepare a 5.0% GA crosslinker aqueous solution and completely immerse the constructed multilayer structure-coated 5-ALA in the GA solution to ensure that the film layer is in full contact with GA. The reaction time is 1 hour at room temperature. After the reaction is completed, the multilayer film is removed from the GA solution and thoroughly washed with a large amount of deionized water to remove unreacted GA. After washing, place it in a ventilated and dry environment to dry naturally. Obtain a layer-by-layer assembled 5-ALA photosynthesis enhancer.

[0041] Example 2

[0042] Nano-supported layer-by-layer self-assembled DAC for CO capture 2 The preparation method of the photosynthesis agent comprises the following steps:

[0043] Preparation of initial layer 5-ALA: SiO 2 NPs were dispersed in AcB buffer with a pH of 5.0 at a concentration of 10 mg / mL, and chitosan solution (1 mg / mL) was added and stirred for 12 h to allow chitosan to adsorb on the SiO 2 NPs surface; 5-ALA was added to the dispersion at a concentration of 1 mg / mL and stirred for 6 hours to form an initial 5-ALA layer.

[0044] Layer-by-layer self-assembly of 5-ALA initial layer: dissolve chitosan in a 10% ethanol deionized water solution to obtain a chitosan polymer solution with a concentration of 1 mg / mL; use 1M NaOH solution to adjust the pH value to 5.0; dissolve SA in ethanol deionized water to obtain a SA polymer solution with a concentration of 1 mg / mL; use 1M HCl solution to adjust the pH value to 5.5.

[0045] Add SA (1 mg / mL, pH 5.5) solution to the surface of the initial layer of 5-ALA, mix thoroughly with a magnetic stirrer, and let it stand to form the first layer of SA coating. Use deionized water to wash the unadsorbed SA to ensure the integrity of each layer. Then add the mixture to the chitosan (1 mg / mL, pH 5.0) polymer material aqueous solution, stir and stand in the same way to form the second layer of chitosan coating. Alternate deposition, each layer reacts for 30 minutes, repeat 6 times, and finally form a multilayer structure. Use a centrifuge (8000 rpm, 10 minutes) to discard the supernatant and separate the 5-ALA coated with the multilayer structure.

[0046] HCHO treatment to obtain layer-by-layer assembled 5-ALA photosynthesis enhancer: Take 100 mL of deionized water, add 5.0 grams of HCHO, and stir evenly. Prepare a 5.0% HCHO crosslinker aqueous solution and completely immerse the constructed multilayer structure-coated 5-ALA in the HCHO solution to ensure that the film layer is in full contact with the HCHO. The reaction time is 1 hour at room temperature. After the reaction is completed, the multilayer film is removed from the HCHO agent solution and thoroughly washed with a large amount of deionized water to remove unreacted HCHO. After washing, place it in a ventilated and dry environment to dry naturally. Obtain a layer-by-layer assembled 5-ALA photosynthesis enhancer.

[0047] Example 3

[0048] Nano-supported layer-by-layer self-assembled DAC for CO capture 2 The preparation method of the photosynthesis agent comprises the following steps:

[0049] Preparation of the initial layer of 5-ALA: AuNPs were dispersed in HEPES buffer at pH 7.2 at a concentration of 10 mg / mL, PDDA solution of 1 mg / mL was added, and stirred for 12 hours; 5-ALA was added to the dispersion at a concentration of 1 mg / mL, and the reaction was stirred for 6 hours to form an initial layer of 5-ALA.

[0050] Layer-by-layer self-assembly of 5-ALA initial layer: Dissolve PDDA in a 10% ethanol deionized water solution to obtain a 1 mg / mL PDDA polymer solution. Use 1M NaOH solution to adjust the pH value to 6.8; Dissolve CMC in ethanol deionized water to obtain a 1 mg / mL CMC polymer solution. Use 1M HCl solution to adjust the pH value to 7.2;

[0051] Add CMC (1 mg / mL, pH 7.2) solution to the surface of the initial 5-ALA layer, use a magnetic stirrer to fully mix, and let it stand to form the first layer of CMC coating; use deionized water to wash the unadsorbed CMC to ensure the integrity of each layer; then add the mixture to the PDDA (1 mg / mL, pH 6.8) polymer material aqueous solution, stir and stand to form the second layer of PDDA coating. Alternate deposition, each layer reacts for 30 minutes, repeat 6 times, and finally form a multilayer structure. Use a centrifuge (8000rpm, 10 minutes) to discard the supernatant and separate the 5-ALA coated with the multilayer structure.

[0052] EDA treatment to obtain layer-by-layer assembled 5-ALA photosynthesis enhancer: Take 100 mL of deionized water, add 5.0 grams of EDA, and stir evenly. Prepare a 5.0% EDA crosslinker aqueous solution and completely immerse the constructed multilayer structure-coated 5-ALA in the EDA solution to ensure that the film layer is in full contact with EDA. The reaction time is 1 hour at room temperature. After the reaction is completed, the multilayer film is removed from the EDA solution and thoroughly washed with a large amount of deionized water to remove unreacted EDA. After washing, place it in a ventilated and dry environment to dry naturally. Obtain a layer-by-layer assembled 5-ALA photosynthesis enhancer.

[0053] Example 4

[0054] Nano-supported layer-by-layer self-assembled DAC for CO capture 2 The preparation method of the photosynthesis agent comprises the following steps:

[0055] Preparation of the initial layer of 5-ALA: ZnONPs were dispersed in Tris-HCl buffer at pH = 7.4 at a concentration of 10 mg / mL; 1 mg / mL of PAEE solution was added and stirred for 12 hours to allow chitosan to adsorb on the surface of ZnONPs. 5-ALA was added to the dispersion at a concentration of 1 mg / mL and stirred for 6 hours to form an initial layer of 5-ALA.

[0056] Layer-by-layer self-assembly of 5-ALA initial layer: PAEE was dissolved in a 10% ethanol deionized water solution to obtain a PAEE polymer solution with a concentration of 1 mg / mL. 1M NaOH solution was used to adjust the pH value to 6.8. PAMPS was dissolved in ethanol deionized water to obtain a PAMPS polymer solution with a concentration of 1 mg / mL. 1M HCl solution was used to adjust the pH value to 7.0.

[0057] Add PAMPS (1 mg / mL, pH 7.0) solution to the surface of the initial layer of 5-ALA, mix thoroughly with a magnetic stirrer, and let it stand to form the first layer of PAMPS coating. Use deionized water to wash the unabsorbed PAMPS to ensure the integrity of each layer. Then add the mixture to the PAEE (1 mg / mL, pH 6.8) polymer material aqueous solution, stir and stand in the same way to form the second layer of PAEE coating. Alternate deposition, each layer reacts for 30 minutes, repeat 6 times, and finally form a multilayer structure. Use a centrifuge (8000 rpm, 10 minutes) to discard the supernatant and separate the 5-ALA coated with the multilayer structure.

[0058] PNB treatment to obtain layer-by-layer assembled 5-ALA photosynthesis enhancer: Take 100 mL of deionized water, add 5.0 grams of PNB, and stir evenly. Prepare a 5.0% PNB crosslinker aqueous solution. Completely immerse the constructed multilayer structure-coated 5-ALA in the PNB solution to ensure that the membrane layer is in full contact with the PNB. The reaction time is 1 hour at room temperature. After the reaction is completed, remove the multilayer film from the PNB solution and wash it thoroughly with a large amount of deionized water to remove unreacted PNB. After washing, place it in a ventilated and dry environment to dry naturally. Obtain a layer-by-layer assembled 5-ALA photosynthesis enhancer.

[0059] Example 5

[0060] Nano-supported layer-by-layer self-assembled DAC for CO capture 2 The preparation method of the photosynthesis agent comprises the following steps:

[0061] Preparation of the initial layer of 5-ALA: PLGANPs were dispersed in NaAc / HAc buffer at pH = 4.79 at a concentration of 10 mg / mL, 1 mg / mL of PLL solution was added, and stirred for 12 hours; 5-ALA was added to the dispersion at a concentration of 1 mg / mL, and the reaction was stirred for 6 hours to form a 5-ALA initial layer.

[0062] Layer-by-layer self-assembly of 5-ALA initial layer: PLL was dissolved in a 10% ethanol deionized water solution to obtain a PLL polymer solution with a concentration of 1 mg / mL. 1M NaOH solution was used to adjust the pH value to 6.7. γ-PGA was dissolved in ethanol deionized water to obtain a γ-PGA polymer solution with a concentration of 1 mg / mL. 1M HCl solution was used to adjust the pH value to 7.1.

[0063] Add PLL (1 mg / mL, pH 6.7) solution to the surface of the initial 5-ALA layer, mix thoroughly with a magnetic stirrer, and let it stand to form the first layer of PLL coating. Use deionized water to wash the unadsorbed PLL to ensure the integrity of each layer. Then add the mixture to the γ-PGA (1 mg / mL, pH 7.1) polymer material aqueous solution, stir and stand in the same way to form the second layer of γ-PGA coating. Alternate deposition, each layer reacts for 30 minutes, repeat 6 times, and finally form a multilayer structure. Use a centrifuge (8000 rpm, 10 minutes) to discard the supernatant and separate the 5-ALA coated with the multilayer structure.

[0064] EGDMA treatment to obtain layer-by-layer assembled 5-ALA photosynthesis enhancer: Take 100 mL of deionized water, add 5.0 grams of EGDMA, and stir evenly. Prepare a 5.0% EGDMA crosslinker aqueous solution. Completely immerse the constructed multilayer structure-coated 5-ALA in the EGDMA solution to ensure that the film layer is in full contact with EGDMA. The reaction time is 1 hour at room temperature. After the reaction is completed, remove the multilayer film from the EGDMA solution and wash it thoroughly with a large amount of deionized water to remove unreacted EGDMA. After washing, place it in a ventilated and dry environment to dry naturally. Obtain a layer-by-layer assembled 5-ALA photosynthesis enhancer.

[0065] Example 6

[0066] Nano-supported layer-by-layer self-assembled DAC for CO capture 2 The preparation method of the photosynthesis agent comprises the following steps:

[0067] Preparation of the initial layer of 5-ALA: AgNPs were dispersed in SCB buffer at pH = 5.0 at a concentration of 10 mg / mL, and 1 mg / mL of PPVAm solution was added, and stirred for 12 hours; 5-ALA was added to the dispersion at a concentration of 1 mg / mL, and stirred for 6 hours to form a 5-ALA initial layer. The pH of the 5-ALA initial layer solution was adjusted to 7.0 to ensure its stability.

[0068] Layer-by-layer self-assembly of 5-ALA initial layer: PVAm was dissolved in a 10% ethanol deionized water solution to obtain a PVAm polymer solution with a concentration of 1 mg / mL. A 1M NaOH solution was used to adjust the pH value to 6.8. SH was dissolved in ethanol deionized water to obtain a SH polymer solution with a concentration of 1 mg / mL. A 1M HCl solution was used to adjust the pH value to 7.0.

[0069] Add SH (1 mg / mL, pH 7.0) solution to the surface of the initial layer of 5-ALA, mix thoroughly with a magnetic stirrer, and let it stand to form the first layer of SH coating. Use deionized water to wash the unadsorbed SH to ensure the integrity of each layer. Then add the mixture to the PVAm (1 mg / mL, pH 6.8) polymer material aqueous solution, stir and stand in the same way to form a second layer of PVAm coating. Alternate deposition, each layer reacts for 30 minutes, repeat 6 times, and finally form a multilayer structure. Use a centrifuge (8000 rpm, 10 minutes) to discard the supernatant and separate the 5-ALA coated with the multilayer structure.

[0070] DSS treatment to obtain layer-by-layer assembled 5-ALA photosynthesis enhancer: Take 100 mL of deionized water, add 5.0 grams of DSS, and stir evenly. Prepare a 5.0% DSS crosslinker aqueous solution and completely immerse the constructed multilayer structure-coated 5-ALA in the DSS solution to ensure that the film layer is in full contact with the DSS. The reaction time is 1 hour at room temperature. After the reaction is completed, remove the multilayer film from the DSS solution and wash it thoroughly with a large amount of deionized water to remove unreacted DSS. After washing, place it in a ventilated and dry environment to dry naturally. Obtain a layer-by-layer assembled 5-ALA photosynthesis enhancer.

[0071] Example 7

[0072] Nano-supported layer-by-layer self-assembled DAC for CO capture 2 The preparation method of the photosynthesis agent comprises the following steps:

[0073] Preparation of the initial layer of 5-ALA: CNTs were dispersed in TritonX-100 buffer at pH 7.0 at a concentration of 10 mg / mL. P4VP solution 1 mg / mL was added and stirred for 12 hours to allow chitosan to adsorb on the surface of CNTs; 5-ALA was added to the dispersion at a concentration of 1 mg / mL and stirred for 6 hours to form an initial layer of 5-ALA.

[0074] Layer-by-layer self-assembly of 5-ALA initial layer: P4VP was dissolved in a 10% ethanol deionized water solution to obtain a P4VP polymer solution with a concentration of 1 mg / mL. A 1M NaOH solution was used to adjust the pH value to 6.5. PSS was dissolved in ethanol deionized water to obtain a PSS polymer solution with a concentration of 1 mg / mL. A 1M HCl solution was used to adjust the pH value to 7.0.

[0075] Add PSS (1 mg / mL, pH 7.0) solution to the surface of the initial 5-ALA layer, mix thoroughly with a magnetic stirrer, and let it stand to form the first layer of PSS coating; use deionized water to wash the unadsorbed PSS to ensure the integrity of each layer. Then add the mixture to the P4VP (1 mg / mL, pH 6.5) polymer material aqueous solution, stir and stand to form the second layer of P4VP coating; alternate deposition, each layer reacts for 30 minutes, repeat 6 times, and finally form a multilayer structure. Use a centrifuge (8000 rpm, 10 minutes) to discard the supernatant and separate the 5-ALA coated with the multilayer structure.

[0076] EDC treatment to obtain layer-by-layer assembled 5-ALA photosynthesis enhancer: Take 100mL of deionized water, add 5.0 grams of EDC, and stir evenly; prepare a 5.0% EDC crosslinker aqueous solution and completely immerse the constructed multilayer structure-coated 5-ALA in the EDC solution to ensure that the film layer is in full contact with the EDC. The reaction time is 1 hour at room temperature; after the reaction is completed, the multilayer film is taken out of the EDC solution, thoroughly washed with a large amount of deionized water to remove the unreacted EDC, and after washing, placed in a ventilated and dry environment to dry naturally. The layer-by-layer assembled 5-ALA photosynthesis enhancer is obtained.

[0077] Experimental Examples 1 to 7 in Table 1 are the physical and chemical properties of 5-ALA (free 5-ALA) in which the initial layer and CK are not immobilized nanoparticles in Examples 1 to 7. Experimental Examples 1 to 7 in Table 2 are the application performances of 5-ALA in which the initial layer and CK are not immobilized nanoparticles in Examples 1 to 7.

[0078] Table 1.5- Physical and chemical properties of ALA before and after immobilization (initial layer)

[0079]

[0080] As can be seen from Table 1 above, the physical and chemical properties of 5-ALA and its derivatives change before and after being immobilized by nanoparticles. The average particle size and particle size distribution of the nanoparticles are significantly reduced (which is conducive to adsorption and absorption), the surface potential is significantly reduced, the hydrophilicity is high, and the stability is significantly improved.

[0081] Table 2.5-Comparison of application performance of ALA before and after solidification (initial layer)

[0082]

[0083] It can be seen from Table 2 above that the initial layer structure established by immobilization significantly enhances the photosensitivity, targeting, and bioavailability of 5-ALA, and significantly reduces the phototoxicity. The above-mentioned nanoparticle immobilization has a substantial improvement effect on the performance of 5-ALA.

[0084] Experimental Examples 1 to 7 in Table 3 are the carbon dioxide absorption performance of plants (tomato) by the initial layer and CK, which are 5-ALA without immobilized nanoparticles (free 5-ALA), in Examples 1 to 7. CK2 is a control group without 5-ALA; CK1 is a control group with 5-ALA without immobilized nanoparticles (free 5-ALA).

[0085] Table 3.5- ALA before and after immobilization (initial layer) on plant (tomato) carbon dioxide absorption

[0086]

[0087]

[0088] Note: Carbon dioxide absorption rate (μmol / m 2 / s): indicates the amount of carbon dioxide absorbed by the plant per unit area per unit time. Reactive oxygen produced by photosensitivity reaction (relative amount): relative to the reactive oxygen production of the control group, used to indicate the intensity of the photosensitivity reaction induced by 5-ALA. Increased photosynthesis efficiency (%): the percentage increase in photosynthesis efficiency relative to the control group.

[0089] Analyze the data in Table 3:

[0090] 1. Ordinary 5-ALA group (CK1): Compared with the control blank group (CK2 without 5-ALA), the carbon dioxide absorption rate of plants using ordinary 5-ALA increased by 50%, indicating that 5-ALA has a significant promoting effect on plant photosynthesis.

[0091] 2. 5-ALA-immobilized nanoparticle group: Compared with the ordinary CK1 group, the use of 5-ALA-immobilized nanoparticle group further significantly improved the carbon dioxide absorption rate of plants, reaching an increase of ≥150%; this is because the present invention uses nanoparticles to immobilize through a specific system, which improves the stability and bioavailability of 5-ALA, while enhancing its photosensitivity, making the production of active oxygen higher, thereby greatly improving the photosynthesis efficiency of plants.

[0092] 3. Net photosynthetic rate (Pn): The nanoparticle carrier combined with 5-ALA treatment group showed a significantly higher net photosynthetic rate, which indicates that this treatment can effectively improve the CO2 absorption and utilization efficiency of plants.

[0093] 4. Stomatal conductance (Gs): The stomatal conductance of the 5-ALA-immobilized nanoparticle group was also significantly improved, indicating that the treatment improved the plant's ability to regulate stomatal opening and closing, thereby optimizing the absorption of CO2.

[0094] 5. Intercellular CO2 concentration (Ci): The intercellular CO2 concentration of the 5-ALA-immobilized nanoparticle group was relatively low, indicating that more CO2 was fixed and participated in the photosynthesis process, reflecting the enhanced CO2 utilization rate.

[0095] 6. Chlorophyll content: The chlorophyll content of the 5-ALA-immobilized nanoparticle group increased, indicating that the effectiveness of the photosensitizer precursor (5-ALA) was improved, thereby enhancing the efficiency of photosynthesis.

[0096] 7. Biomass accumulation: The biomass accumulation of the 5-ALA-immobilized nanoparticle group was significantly higher than that of CK and CK1, indicating that this method can effectively promote plant growth and yield.

[0097] 8. Carbon dioxide assimilation: Through calculation, the CO2 assimilation of the treatment group was significantly higher than that of the control group, which further supports the positive effect of nanoparticle carrier combined with 5-ALA on enhancing plant CO2 absorption and photosynthesis.

[0098] in conclusion

[0099] From the data in Table 3 above, it can be seen that the use of nanoparticles as carriers combined with 5-ALA or its derivatives can significantly improve the photosynthesis efficiency, CO2 absorption capacity and biomass accumulation of plants. This shows that this method has potential application value in the fields of agriculture and ecology, especially in improving crop yields and carbon fixation capacity.

[0100] Tables 4 and 5 show the physicochemical properties and photosynthesis performance of the stable and functionalized multilayer structures coated with 5-ALA prepared by layer-by-layer self-assembly in Experimental Examples 1-1 to 1-7 in Examples 1 to 7 of the present invention. The self-assembled film can be made more stable in the plant body and not easily degraded by adjusting the number of layers or chemical properties of the film, thereby extending the effective action time of 5-ALA and achieving a slow release of 5-ALA. This slow-release effect can ensure the continuous action of 5-ALA in the plant body and avoid waste or toxicity caused by a one-time high-concentration application. Since the layer-by-layer self-assembled structure can accurately control the distribution of 5-ALA at the nanoscale, it can be directly directed to the photosynthesis reaction center in the plant chloroplast, improving its utilization rate, thereby significantly enhancing the photosynthesis efficiency of the plant.

[0101] Table 4. Physical and chemical properties of layer-by-layer self-assembled 5-ALA

[0102]

[0103] By comparing Table 1 and Table 4, we can compare the changes in the physical and chemical properties of layer-by-layer self-assembled 5-ALA. The size of the nanoparticles is suitable, the stability is significant, and the 5-ALA loading capacity is also significantly improved.

[0104] Table 5. Photosynthesis performance of layer-by-layer self-assembled 5-ALA

[0105]

[0106]

[0107] Analyze and compare the data in Table 3 and Table 5:

[0108] 1. Net photosynthetic rate (Pn): The layer-by-layer self-assembled 5-ALA treatment group showed a significantly higher net photosynthetic rate, which indicates that this treatment can effectively improve the CO2 absorption and utilization efficiency of plants.

[0109] 2. Stomatal conductance (Gs): The stomatal conductance of the layer-by-layer self-assembled 5-ALA treatment group was also significantly improved, indicating that this treatment may have improved the plant's ability to regulate stomatal opening and closing, thereby optimizing the absorption of CO2.

[0110] 3. Intercellular CO2 concentration (Ci): The intercellular CO2 concentration in the LBL self-assembled 5-ALA-treated group was relatively low, indicating that more CO2 was fixed and participated in the photosynthesis process, reflecting the enhanced CO2 utilization rate.

[0111] 4. Chlorophyll content: The chlorophyll content of the layer-by-layer self-assembled 5-ALA treatment group increased, indicating that the effectiveness of the photosensitizer precursor (5-ALA) was improved, thereby enhancing the efficiency of photosynthesis.

[0112] 5. Biomass accumulation: The biomass accumulation of the layer-by-layer self-assembled 5-ALA treatment group was significantly higher than that of the control group, indicating that this method can effectively promote plant growth and yield.

[0113] 6. Carbon dioxide assimilation: Through calculation, the CO2 assimilation amount of the layer-by-layer self-assembled 5-ALA treatment group was significantly higher than that of the control group, which further supports the positive effect of layer-by-layer self-assembled 5-ALA on enhancing plant CO2 absorption and photosynthesis.

[0114] The ALA nanocapsule photosynthetic enhancer prepared by the layer-by-layer self-assembly method has efficient and stable photosynthetic performance, and shows a plant growth regulating effect that is significantly better than traditional ALA preparations and untreated controls.

[0115] Table 6 shows the photosynthetic performance indexes of 5-ALA after layer-by-layer self-assembly after cross-linking treatment in Examples 1 to 7 of the present invention.

[0116] Table 6. Photosynthetic performance of 5-ALA after cross-linking treatment (layer-by-layer self-assembly)

[0117]

[0118] Comparative analysis of Table 5 and Table 6

[0119] 1. Photosynthetic rate: refers to the CO per unit area of ​​leaves in a fixed time. 2 The data showed that the photosynthetic agent after cross-linking significantly increased the photosynthetic rate.

[0120] 2. Chlorophyll content: used to evaluate the accumulation of chlorophyll in leaves. The chlorophyll content of samples after cross-linking treatment increased, indicating that the efficiency of photosynthesis was improved.

[0121] 3.5-ALA release rate: indicates the amount of 5-ALA released per day. The release rate of the sample after cross-linking treatment is lower, indicating that it can delay the release and maintain the effect for a longer time.

[0122] 4. Long-term stability: The stability of the samples after cross-linking treatment is significantly improved in long-term use, and the service life is extended.

[0123] 5. Multilayer film stability: The durability of the multilayer film in practical applications. The cross-linking treatment significantly improves the stability of the multilayer film.

[0124] 6. Initial photosynthesis enhancement effect: The percentage increase in the photosynthesis capacity of the treated plants compared to the untreated control in Table 6.

[0125] 7. Photosynthesis maintenance time: The duration that 5-ALA photosynthesis agent maintains the photosynthesis promoting effect on plants.

[0126] It can be seen from the table data that the cross-linking treatment significantly improved the use effect and stability of 5-ALA photosynthesis agent.

[0127] Table 7 shows the effect of the photosynthetic agent of 5-ALA after layer-by-layer self-assembly after crosslinking treatment of Examples 1 to 7 of the present invention on planting performance. CK2 in Table 7 is a control group without 5-ALA, and CK1 is a control group of 5-ALA without immobilized nanoparticles (free 5-ALA).

[0128] Directions of administration:

[0129] 1. The application concentration of ALA in all groups was the same, 50 mg / L.

[0130] 2. Application method: foliar spraying

[0131] 3. Experimental period: 60 days

[0132] Table 7. Effect of 5-ALA photosynthetic agent planting after cross-linking treatment (layer-by-layer self-assembly)

[0133]

[0134]

[0135] From Table 7 above, it can be concluded that Examples 1 to 7 of the present invention are significantly better than the self-state ALA preparation in the application of crops (wheat and tomatoes). Its advantages are manifested in higher plant growth rate, enhanced photosynthesis capacity, better yield and fruit quality. It can be seen from the data that after cross-linking treatment (layer-by-layer self-assembly), 5-ALA not only promotes plant growth, but also significantly improves the economic value of crops.

[0136] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a nano-solidified layer-by-layer self-assembled DAC CO2 capture photosynthesis agent, characterized in that: The following steps are involved: Step (1), dispersing the nanoparticle carrier in a buffer solution, adding a positively charged polymer solution or a negatively charged polymer solution to obtain a nanomaterial with a surface adsorbed polymer, and adding 5-ALA with stirring to form a 5-ALA initial layer; Step (2), according to the positive and negative surface charges of the 5-ALA initial layer in step (1), polymer materials with opposite charges are deposited alternately in sequence, and stirred for self-assembly to form coated 5-ALA coated with multiple layers of polymer materials; Step (3), adding the coated 5-ALA described in step (2) to the crosslinker solution, the crosslinker reacts with the polymer groups of the membrane layer to form a crosslinked structure, and drying to obtain a nano-solidified layer-by-layer self-assembled DAC CO2 capture photosynthesis agent.

2. The method for preparing a nano-solidified layer-by-layer self-assembled DAC CO2 capture photosynthesis agent according to claim 1, characterized in that: The nanoparticle carrier in step (1) is any one of gold nanoparticles, iron oxide nanoparticles, silicon dioxide nanoparticles, polylactic acid-glycolic acid copolymer nanoparticles, silver nanoparticles, carbon nanotubes, and zinc oxide nanoparticles.

3. The method for preparing a nano-solidified layer-by-layer self-assembled DAC CO2 capture photosynthesis agent according to claim 1, characterized in that: The buffer in step (1) is any one of phosphate buffer, acetate buffer, HEPES buffer, Tris-HCl buffer, sodium citrate buffer, TritonX-100, and sodium acetate-acetic acid buffer.

4. The method for preparing a nano-solidified layer-by-layer self-assembled DAC CO2 capture photosynthesis agent according to claim 1, characterized in that: The nanoparticle carrier is dispersed in the buffer solution at a mass volume concentration of 5 mg / mL-10 mg / mL.

5. The method for preparing a nano-solidified layer-by-layer self-assembled DAC CO2 capture photosynthesis agent according to claim 1, characterized in that: The polymer material in the positively charged polymer solution in step (1) or step (2) is any one of chitosan, polyethyleneimine, polydimethyldiallylammonium chloride, poly-L-lysine, polyvinyl alcoholamine, poly(4-vinylpyridine), and poly(2-acrylamidoethylamine); the polymer material in the negatively charged polymer solution is any one of sodium alginate, sodium hyaluronate, polyacrylic acid, sodium carboxymethyl cellulose, sodium polystyrene sulfonate, sodium polyacrylamide sulfonate, and sodium polyglutamate.

6. The method for preparing a nano-solidified layer-by-layer self-assembled DAC CO2 capture photosynthesis agent according to claim 6, characterized in that: The positively charged polymer solution is an ethanol solution of a polymer material; and the negatively charged polymer solution is a deionized water solution of a polymer material.

7. The method for preparing a nano-solidified layer-by-layer self-assembled DAC CO2 capture photosynthesis agent according to claim 6, characterized in that: The mass volume concentration of the positively charged polymer solution or the negatively charged polymer solution is 1 mg / mL, and the pH value of both is adjusted to 6.5-7.5 using NaOH solution or HCl solution.

8. The method for preparing a nano-solidified layer-by-layer self-assembled DAC CO2 capture photosynthesis agent according to any one of claims 1 to 7, characterized in that: The cross-linking agent in step (3) is any one of glutaraldehyde, formaldehyde, ethylenediamine, p-dithiodibenzoic acid, N-ethyl-N'-(3-dimethylaminopropyl)carbodiimide, ethylene glycol dimethacrylate, and 4-nitroanisole.

9. The method for preparing a nano-solidified layer-by-layer self-assembled DAC CO2 capture photosynthesis agent according to claim 8, characterized in that: The mass percentage concentration of the cross-linking agent is 5.0%.

10. The method for preparing a nano-solidified layer-by-layer self-assembled DAC CO2 capture photosynthesis agent according to claim 8, characterized in that: The cross-linking reaction in step (3) is carried out at room temperature for 1-2 hours. After the reaction is completed, the multi-layer film with a cross-linked structure is taken out from the cross-linking agent solution, washed thoroughly with deionized water, and dried naturally, under ventilation or at a low temperature below 50°C.